ISLAMIC PERSPECTIVE IN WASTE MANAGEMENT - Bismantara Bismantara; Eva Kurnia; Sofian Akmal (STIESA Press, 2024)
The waste problem has become a serious problem in various provinces throughout Indonesia, including West Java Province. The waste problem is not a problem that can be avoided, but must be overcome. A strategic, comprehensive and sustainable effort must be made to deal with the waste problem so that in the process new problems do not arise. According to the Regulation of the Minister of Environment of the Republic of Indonesia Number 13 of 2012 concerning Guidelines for Implementing Reduce, Reuse and Recycle through Waste Banks, waste banks are places for sorting and collecting recyclable waste that has economic value. That is the aim of building a waste bank as a strategy to build public awareness so that they can be 'friends' with waste to gain direct economic benefits from waste. With this pattern, residents apart from being disciplined in managing waste also get additional income from the rubbish they collect. Good waste management is a real form of maintaining cleanliness